ANALISIS KEBUTUHAN PENGEMBANGAN MULTIMEDIA INTERAKTIF SEBAGAI MEDIA PEMBELAJARAN IPAS KELAS V SD - Fauziah, Raihanah; Respati, Resa; Mohamad Setiadi, Pidi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to analyze the need for interactive multimedia development as a medium for learning IPAS for grade V elementary school. The research subjects consisted of fifth grade teachers and students at SDN 1 Nagarawangi and SDN 2 Nagarawangi. Data collection techniques were carried out through observation, interviews, and documentation using prepared guidelines. Data analysis used a qualitative descriptive method with reference to the Miles and Huberman model. The preliminary findings showed several important points, namely: (1) there is a need for learning media that better supports the IPAS learning process; (2) IPAS learning is still considered difficult to understand by students because the material is abstract; (3) students need interesting and innovative interactive multimedia, especially in IPAS learning; and (4) interactive multimedia is seen as the right solution to deliver material on the topic effectively. Thus, the researcher concludes that in this study, the development of interactive multimedia is needed to facilitate and increase students' interest in learning IPAS grade 5.